Risk Factors Causing Stunting in Toddlers: A Literature Review - Shofiyah, Alya; Windarti, Siti Wahyu (Faculty of Medical - UPN Veteran Jawa Timur, 2024)
Stunting is a condition in which a child experiences a lack of nutritional intake for a long period of time, causing growth disorders in toddlers (infants under five years old). Stunting in toddlers is a global health problem that is influenced by various social, economic, and policy factors. Objective. This study aims to conduct a systematic review of the available literature to identify risk factors for stunting and examine the challenges faced in handling it, especially in developing countries such as Indonesia and South Africa. In addition, this study also focuses on the role of social policy and health interventions in preventing stunting. Methods. A literature search was conducted on several reputable scientific databases, such as PubMed, Web of Science, and Google Scholar with a span of 2019-2024. Keywords used include